2017
DOI: 10.3390/su9020187
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factors Driving Seasonal Farmland Abandonment: A Case Study at the Regional Level in Hunan Province, Central China

Abstract: Farmland abandonment, including perennial and seasonal abandonment, is an important process of land use change that matters most to food security. Although there is a great deal of studies on farmland abandonment, seasonal abandonment, which is as serious as perennial abandonment, has attracted little academic attention. This paper takes Hunan Province in central China as its study area and uses a spatial regression model to examine the driving factors of seasonal farmland abandonment at the county level. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Boncinelli et al found that proximity reduces transaction and information costs [45]. Studies in China also showed that agglomeration of population, industries and technology affected on spatial pattern of farmland [48,49]. These evidences, however, are mostly based on county level data [47], rural household level data [46], and plot level data [50].…”
Section: Research Frameworkmentioning
confidence: 98%
“…Boncinelli et al found that proximity reduces transaction and information costs [45]. Studies in China also showed that agglomeration of population, industries and technology affected on spatial pattern of farmland [48,49]. These evidences, however, are mostly based on county level data [47], rural household level data [46], and plot level data [50].…”
Section: Research Frameworkmentioning
confidence: 98%
“…These features take factors such as altitude, slope, fertility, soil erosion, climate, and climate change into consideration. Several authors show that where the natural environment is less suitable, there is an increase in the risk of agricultural land being abandoned [17,20,22,29].…”
Section: Drivers Of Farmland Abandonmentmentioning
confidence: 99%
“…Intensive social transformations-demographic, economic, and political-leave their mark upon the traditional rural life [40,41]. Currently, depopulation and the traditional agriculture abandonment represent a global interest for researchers and policy makers at different levels [42].…”
Section: Discussionmentioning
confidence: 99%